Bolivia (Journal of Parents and Teachers, 2026)
Bolivia is a land marked by its geographical reality. The height of the Andean peaks and the Amazonian jungles is home to most of its inhabitants. It was the last continental territory to achieve independence, which began with the Battle of Ayacucho. One of the most important regions was Upper Peru, where the city of Charcas was founded, later renamed La Plata due to its wealth in silver, the exploitation of which eventually depleted the mineral. Bolivian fauna is unique, especially around Lake Titicaca. Finally, we can find camels without humps: llamas, alpacas, vicuñas and guanacos, characteristic of these Andean lands.
Keywords: Bolivia; history; Plata; Lake Titicaca; wildlife